Utilizador:Thiago Marcel/Mestrado/Análise/Números Reais: diferenças entre revisões

 
== 2 ==
Dado <math>a \ne 0</math> num corpo K, põe-se, por definição, <math> a^0 = 1 </math> e, se <math> n \in \mathbb{N}, a^{-n} = {1 \over a^n}, \mbox{ ou seja}, a^{-n}=(a^n)^{-1}. </math> Sejam quais forem <math> m, n \in \mathbb{Z} ,</math> prove :
* <math> a^m \cdot a^n = a^{m+n}. </math>
 
* <math> (a^m)^n = a^{mn} </math>
=== Resolução ===
* <math> a^m \cdot a^n = \underbrace{ a \cdot a \cdot...\cdot a }_{ m } \cdot \underbrace{ a \cdot a \cdot...\cdot a }_{n} = \underbrace{ a \cdot a \cdot...\cdot a }_{m+n} = a^{m+n}. </math>
* <math> (a^m)^n = (\underbrace{ a \cdot a \cdot...\cdot a }_{m} )^n = \underbrace{ \underbrace{ a \cdot a \cdot...\cdot a }_{m} \cdot \underbrace{ a \cdot a \cdot...\cdot a }_{m} \cdot ... \cdot \underbrace{ a \cdot a \cdot...\cdot a }_{m}}_{n} = \underbrace{ a \cdot a \cdot...\cdot a }_{\underbrace{m+m+...+m}_{n}} = \underbrace{ a \cdot a \cdot...\cdot a }_{mn} = a^{mn} </math>
 
== 3 ==
3 415

edições